Tertiary Surgery for Complicated Repair of Esophageal Atresia - Ortiz, Ruben; Galán, Alba Sánchez; Martinez, Leopoldo; Dominguez, Eva; Hernández, Francisco; Santamaria, Manuel Lopez; Tovar, Juan Antonio (European Journal of Pediatric Surgery, 2015)
Aim The ideal repair of esophageal atresia (EA) is primary anastomosis with closure of the fistula if present. Long gap or local circumstances prompt other procedures that occasionally lead to disastrous complications. The aim of this study was to analyze the management of these complications in a tertiary referral center.Patients and Methods A retrospective review of patients treated for EA between 1993 and 2013 was conducted. Both the patients were primarily treated by us, and referrals from elsewhere after two or more failed operations were included.Results In total, 23 patients were included (3/176 cases of EA treated primarily by us and 20 referrals). Of the 23 patients, 6 had type I EA, 15 type III (four long gaps), 1 type IV, and 1 type V. Cardiac anomalies were associated in seven cases, duodenal atresia in three, and Down syndrome in two patients. Primary anastomosis was initially achieved in 12 patients. Primary or secondary Foker lengthening was used in seven cases. The causes of the failure were anastomotic leaks in nine, unmanageable strictures in seven, and refistulization in five patients. These patients required 66 reoperations (median of 3 [2–7]) before inclusion in the study. Radical tertiary treatment consisted of 15 esophageal replacements (11 colonic grafts and 4 gastric pull-ups), and 1 esophageal-gastric disconnection. Five patients previously treated with esophageal replacement and referred for graft problems required 13 interventions. Two families did not give consent for one replacement and one disconnection. Complications appeared in 12 patients, and 9 additional operations were required in 7 patients. With a follow-up of 31 months (range, 4–139 months) 15 patients take all their meals per os, 5 occasionally use the gastrostomy, and 2 and 1 are fed exclusively via gastrostomy or jejunostomy. All tracheoesophageal fistulas were closed, but 15 cases are below p3 for weight and 12 for height. Three patients (13%) ultimately died 32 months (range, 9–56 months) after the first operation (due to aspiration in one, and for causes unrelated to it in the other two [tracheostomy obstruction and Guillain–Barré syndrome]).Conclusions When repeated complications appear after EA repair, radical surgical attitudes may be justified. If esophageal continuity cannot be reestablished, the native esophagus may have to be discarded and replaced. Many complications should be expected, but the end result can be good. These patients should be referred to centers with large experience in the management of this complex condition.
Keywords: esophageal atresia; esophageal replacement; long-gap; elongation; complications